2011
DOI: 10.1111/j.1742-4658.2011.08300.x
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone affects the fibroblast growth factor–proteoglycan signaling axis to regulate osteosarcoma cell migration

Abstract: Parathyroid hormone (PTH)(1-34), which has been established to have a dual effect on bone metabolism, was recently found to regulate osteosarcoma cell migration. A significant part of the bone anabolic action of PTH(1-34) is attributed to fibroblast growth factor (FGF)-2 stimulation. Furthermore, it was recently suggested that the FGF-proteoglycan axis may form an extracellular matrix-related regulatory feedback loop that controls osteoblastic lineage cell proliferation and execution of the osteogenic program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Oncomine (Compendia Biosciences, Ann Arbor, MI) was also used for the analysis and visualization of osteosarcoma studies showing FGFR2 mRNA overexpression osteosarcoma biopsy samples compared to other sarcomas [ 108 , 109 ]. Furthermore, a previous study demonstrated that FGF2, an FGFR ligand, upregulated migration in an osteosarcoma cell line [ 110 ]. This is consistent with our results indicating that FGFR2 is phosphorylated and promotes the motility and colony formation of the metastatic LM7 cells.…”
Section: Fgfr2supporting
confidence: 95%
“…Oncomine (Compendia Biosciences, Ann Arbor, MI) was also used for the analysis and visualization of osteosarcoma studies showing FGFR2 mRNA overexpression osteosarcoma biopsy samples compared to other sarcomas [ 108 , 109 ]. Furthermore, a previous study demonstrated that FGF2, an FGFR ligand, upregulated migration in an osteosarcoma cell line [ 110 ]. This is consistent with our results indicating that FGFR2 is phosphorylated and promotes the motility and colony formation of the metastatic LM7 cells.…”
Section: Fgfr2supporting
confidence: 95%
“…Accordingly, several reports describe biglycan-dependent induction of cell migration in various types of non-carcinoma cells [172, 178, 185]. In contrast, in osteosarcoma cells, biglycan reduces migratory capacity [186]. Interestingly, in lung fibroblasts biglycan activates the signaling pathways of RhoA and Rac1 thereby stimulating migration of these cells [185].…”
Section: Biglycan Triggers Inflammation and Tumorigenesismentioning
confidence: 99%
“…Dissection of the sets of genes that control the behavior of Bgn-null pre-osteoblasts using oligonucleotide microarrays revealed that Bgn deficiency affects the genes that control inflammation, immune response, and growth of tumor cells (73). Indeed, biglycan affects osteoblastic tumor cell behavior, as it was recently suggested that osteosarcoma cells utilize Runx2 and the FGF-2/syndecan/heparan sulfate proteoglycan axis, a key effector of the osteogenic program, to regulate their migration in a manner dependent on biglycan expression (74). Furthermore, osteosarcoma markers of poor response to therapy (Huvos grade I/II response defines tumors with little or no response to chemotherapy) are predominantly gene products involved in microenvironmental remodeling and osteoclast differentiation, including Bgn (75).…”
Section: Roles In Bone Tumor Progressionmentioning
confidence: 99%